PERUBAHAN INTENSITAS NYERI TENGKUK AKIBAT HIPERTENSI PADA LANSIA DENGAN IMPLEMENTASI TEKNIK RELAKSASI OTOT PROGRESIF (Studi Kasus di Poli Jantung RS. Militer Kota Malang) - Karunia Friska; Dian Pitaloka Priasmoro; Ruswandi . (Jurnal Kesehatan Hesti Wira Sakti, 2014)
Hypertension is a disease afflicting many societies in Indonesia and every year experience increased. Symptoms are often perceived ranging from dizziness, neck pain and sleep difficult. The public generally still use medical therapy to resolve the issue. However, as an alternative, the public can use the progressive muscle relaxation technique to reduce pain at the nape. This research design using design case studies. Research subject is the elderly aged 45–59 years of age. Have blood pressure  140/90 mmHg accompanied by pain in nape with Lighter scale - is being conducted at the heart poly dr soepraoen hospital. The focus of this research is an effort lose pain nape clients with progressive muscle relaxation technique. This research Data taken with the use of interviews, physical examinations and observations. After the data is collected and then analyzed the content of the material analysis. The results showed a progressive muscle relaxation Technique can be used as an alternative to lower Pain Nape. On the first day the pain scale was reduced from 5 to 3, on the second day the pain scale was reduced from 4 to 2, and on the third day the pain scale was reduced from 4 to 2. See the results of this research community can use the technique of Progressive muscle relaxation as an alternative action to lower non pharmacological pain nape. Keywords: progressive muscle relaxation techniques, pain nape, hypertension